PEMIDANAAN PELAKU USAHA DAN/ATAU KEGIATAN TANPA IZIN LINGKUNGAN (STUDI PENYIDIKAN DIWILAYAH HUKUM POLRESTABES MEDAN) - Prastiyo Triwibowo; Alvi Syahrin; Syamsul Arifin; Madiasa Ablisar (Universitas Sumatera Utara, 2018)
Abstract Implementation of criminalization through mechanism of criminal justice system so as to criminalize business actors and / or activities that are naughty proven to carry out business and / or activity without being equipped with environmental permit which has been obliged in accordance with the law. One of the instruments in an effort to prevent the occurrence of pollution and environmental damage is the environmental permit, as stipulated in Article 1 Number 35 of Law Number 32 Year 2009 on Environmental Protection and Management which further regulated in Government Regulation Number 27 Year 2012 on Environmental Permit. With the existence of Law Number 32 Year 2009 0n Environmental Protection and Management has obliged buiness actors who are required Amdal and UKL-UPL shall have environmental permit. The enforcement of environmental permits in accordance with Government Regulation Number 27 of 2012 likens environmental documents before this Government Regulation as an environmental permit and after this Government Regulation shall be an environmental license. As one of the problems in this research is how the legal arrangement of business actors and / or activities related to environmental permit. The method of research to be conducted in this thesis is normative juridical research. This study was conducted to examine previous studies on legal principles regarding criminalization related to environmental permits. Based on the description above can be concluded that legal arrangements related to environmental permit are contained in article 1 point 35 UUPPLH and article 1 PP. No. 27/2007 concerning environmental permit is a license granted to any person conducting business and/or activity of Amdal or UKL-UPL obligatory in the framework of environmental protection and management as a prerequisite to obtain business license and/or activity. Keywords: Punishment, Environmental Permit, Business actor or activity.